Diversity of the Starch Granule Morphology of Several Types Cassava (Minihot esculenta Crantz) - Via Susana Gusni; Moralita Chatri; Des M; Afifa Akhyar; N.Sri Hartati; Hani Fitriani; Nanang Taryana (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
Cassava (Manihot esculenta Crantz), which is commonly called singkong is multipurpose crop that can be processed as food, feed and other cassava-based bioproduct. Potential application of cassava starch is determined by the properties of starch as the main component of cassava tuber biomass. The size of the cassava starch granules is different for each variety due to genetic and the environment factors in which it grows. The size of the starch granules affects the application of the starch. This study aimed to determine the shape and diameter of the starch granule in several types of cassava through microscopic analysis. The shape and the size of the 62 starch samples tested was varied. The starch granules shape was dominated by spheres form. The diameter of cassava starch granules ranged from 2.016 ± 0.015 µm – 3.318 ± 0.045 µm. The highest diameter was Tidung1.2 and the lowest was Tidung 2.2.